paratexte in specialized literary journals : AL ADEEB AL IRAQI magazine is a model - Abdul Ghaffar Al-Samarrai, Nazar (ALBAHITH ALALAMI, 2022)
Post-structural critical studies highlighted the importance of studying the texts surrounding the text as an important part in the process of receiving and understanding texts, and although this topic was dealt with by the ancient Arabs and Europeans, interest in it appeared clearly after the appearance of Gerard Genet's book (SEUILS), which separated it Text Thresholds. Or what he called paratexte, and dealt with them with interest as he reads them on books. With the development of semiotic studies, interest in paratexte studies began in a broader way and in various literary and non-literary texts, including journalistic texts. And since specialized magazines are one of the press releases that enjoy their privacy in terms of topics and recipients, and are distinguished by the presence of the cover that bears features indicative of the identity of the magazine, the researcher worked on studies of the components of the magazine cover as being parallel texts that the reader/recipient must pass through before accessing the texts published on the pages the number. Literary magazines are specialized magazines that manufacture their paratexte in a way that makes them indicative of specialization, which makes the cover perform a communicative function, informing the recipients of the nature of the topics included in the magazine.The study dealt with the components of the cover of AL ADEEB AL IRAQI(Iraqi literary) magazine issued by the UNION OF Iraq WRITRS, from the semiotic side, to identify the parallel texts that it contains, namely the name of the magazine, the information related to it, the issuer, and the accompanying image, in addition to the titles chosen to appear on the cover.The researcher concluded that the cover of the magazine bears signs indicative of its specialization in one of the fields, and these signs include paratexte (SEUILS) through which the reader passes to the topics published in the magazine, belonging to what is known as the peritetfe editorial text, that is, the text related to the publishing body and not the text writers Published in the magazine.: